Never again? Challenges in transforming the health workforce landscape in post-Ebola West Africa - Barbara McPake; Prarthna Dayal; Christopher H. Herbst (BMC, 2019)
Abstract Background The 2013-2014 West African Ebola outbreak highlighted how the world's weakest health systems threaten global health security and heralded huge support for their recovery. All three Ebola-affected countries had large shortfalls and maldistribution in their health workforce before the crisis, which were made worse by the epidemic. This paper analyzes the investment plans in Liberia, Sierra Leone, and Guinea to strengthen their health workforces and assesses their potential contribution to the re-establishment and strengthening of their health systems. The analysis calculates the plans' costs and compares those to likely fiscal space, to assess feasibility. Methods Public sector payroll data from 2015 from each country was used for the workforce analysis and does not include the private sector. Data were coded into the major cadres defined by the International Standard Classification of Occupations (ISCO-88). We estimated health worker training numbers and costs to meet international health worker density targets in the future and used sensitivity analysis to model hypothetical alternate estimates of attrition, drop-outs, and employment rates. Results Health worker-to-population density targets per 1000 population for doctors, nurses, and midwives are only specified in Liberia (1.12) and Guinea's (0.78) investment plans and fall far short of the regional average for Africa (1.33) or international benchmarks of 2.5 per 1000 population and 4.45 for universal health coverage. Even these modest targets translate into substantial scaling-up requirements with Liberia having to almost double, Guinea quadruple, and Sierra Leone having to increase its workforce by seven to tenfold to achieve Liberia and Guinea's targets. Costs per capita to meet the 2.5 per 1000 population density targets with 5% attrition, 10% drop-out, and 75% employment rate range from US$4.2 in Guinea to US$7.9 in Liberia in 2029, with projected fiscal space being adequate to accommodate the proposed scaling-up targets in both countries. Conclusions Achieving even a modest scale-up of health workforce will require a steady growth in health budgets, a long-term horizon and substantial scale-up of current training institution capacity. Increasing value-for-money in health workforce investments will require more efficient geographical distribution of the health workforce and more consideration to the mix of cadres to be scaled-up.